Analisis Perhitungan Harga Pokok Produksi UMKM Jamu di Kelurahan Rejowingaun Kota Yogyakarta - Suparyati, Dea Susanti; Wardiwiyono, Sartini (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
Micro, Small and Medium Enterprises in running their business sometimes only focus on their sales and pay less attention on fund management so that it becomes an obstacle to growth. The lack of fund management knowledge results in less optimal profit. This study aims to identify production costs of Jamu MSMEs in Rejowinangun Village, Yogyakarta in order to calculate the cost of goods manufactured (COGM) and determine the reasonable selling price. Qualitative and quantitative data were collected through interviews, observation and documentation to allow the researchers to conduct descriptive analysis. The results of the study show that, during 10 years in operation, the business actors in Jamu MSMEs still do not understand how to calculate COGM so it is unknown whether their selling price could covered the costs their have incurred. Furthermore, this study suggests that Jamu MSMEs could adopt full costing or variable costing for calculating COGM. With the right amount of COGM being calculated, the business actors could determine the reasonable selling price of their product so that they may incur their targeted profit.